'Face' and psychological processes of laid-off workers in transitional China. Issue 3 (1st July 2016) - Wang, Bingxin; Greenwood, Kenneth Mark
Abstract : Objective: The objective was to explore the psychological experiences of laid-off workers in contemporary transitional China and to formulate a theoretical model of these. Methods: In-depth interviews of 26 laid-off workers were conducted and analysed using grounded theory techniques. Results: Four themes underline the psychological processes of these laid-off workers – feeling of loss, feeling of physical pain, feeling of fatalism, and final acceptance. These are characterized by Chinese culture and its philosophy – feeling of loss is dominated by their loss of face ( diu mianzi ), physical pain is a somatization of their mental painfulness, their fatalism is traced back to the Chinese ancient theocratic concept of Tian Ming, and their acceptance of reality to their final making face ( zheng mianzi ) is sourced from both Confucianism and Daoism. Conclusion: The psychological experience of laid-off workers (or unemployed workers) is likely to have varied manifestations in different cultural contexts. The psychological processes of Chinese laid-off workers (or unemployed workers) might be different from those of laid-off workers in Western countries. A therapeutic intervention to cater for the needs of laid-off workers derived from the four themes might be effective.